The last kingdom - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2023)
"King Ludwig II of Bavaria was an enigmatic figure who was deposed in 1886, mysteriously drowning three days later. Eccentric to the point of madness, history tells us that in the years before he died Ludwig engaged in a worldwide search for a new kingdom, one separate, apart, and in lieu of Bavaria. A place he could retreat into and rule as he wished. But a question remains: did he succeed? Enter Cotton Malone. After many months, Malone's protégé, Luke Daniels, has managed to infiltrate a renegade group intent on winning Bavarian independence from Germany. Daniels has also managed to gain the trust of the prince of Bavaria, a frustrated second son intent on eliminating his brother, the duke, and restoring the Wittelsbach monarchy, only now with him as king. Everything hinges on a 19th century deed which proves that Ludwig's long-rumored search bore fruit--legal title to lands that Germany, China, and the United States all now want, only for vastly different reasons. In a race across Bavaria for clues hidden in Ludwig's three fairytale castles--Neuschwanstein, Linderhof and Herrenchiemsee--Malone and Daniels battle an ever-growing list of deadly adversaries, all intent on finding the last kingdom"--